The Influence Of Brand Ambassador And Brand Image On The Decision To Purchase Body Lotion Scarlett Whitening (Survey of Scarlett Whitening Consumers in Tasikmalaya City) - Nurapipah, Anitia; Arisman, H Ari; Arif (Universitas Dehasen Bengkulu, 2024)
This research aims to understand and analyze the influence of brand ambassadors and brand image on purchasing decisions for Scarlett Whitening Body Lotion among Scarlett Whitening consumers in Tasikmalaya City. The method used in this research is causality through a survey approach, with a research sample of 100 Scarlett Whitening Body Lotion Consumers in Tasikmalaya City. The data used uses primary data. The analytical tool used in this research is multiple regression using SPSS 26. The results show that Brand Ambassador has a very good classification, Brand Image has a good classification, and Purchase Decisions have a good classification for Scarlett Whitening Consumers in Tasikmalaya City. Together or simultaneously Brand Amassador and Brand Image have a significant influence on Purchasing Decisions. Partially Brand Ambassadors have a significant influence on Purchasing Decisions. And partially, brand image has a significant influence on purchasing decisions for Scarlett Whitening Body Lotion among Scarlett Whitening consumers in Tasikmalaya City.